Investigation of mtDNA control region sequences in a Tibetan population sample from China. (3rd May 2016) - Wang, Yun-ke; Yao, Jun; Han, Xuan; Ding, Mei; Pang, Hao; Wang, Bao-jie; Zhang, Zhi-qiang
Abstract: Mitochondrial hypervariable region sequences including HVI and HVII (15, 751–520) were investigated from 174 unrelated Tibetan individuals living in Tibet Autonomous Region in People's Republic of China. The resulted sequences were aligned and compared with revised Cambridge sequence (rCRS). This sequence variability rendered a high gene diversity value (0.9940 ± 0.0021) and a high random match probability (0.0118) was determined with PIC of 0.9882. Among a total of 174 samples, 217 polymorphic sites were identified, which defined 135 haplotypes. A total of 135 different haplotypes were detected, 113 of them were unique and 22 were shared. The most common haplogroup was M9a1a1c1b1 (16.09%), followed by A11 (6.32%), A (5.17%), R (4.60%), A15 (4.60%), and G3a1 (3.45). The proportions of macro-haplogroups M, N, and L were 54.60%, 42.53%, and 2.87%, respectively. By principal component analysis (PCA), there was no special cluster between Tibetans and other populations except that the structure of Tibetans closely resembled that of Uygur in component 2.